1975
DOI: 10.1093/infdis/131.5.543
|View full text |Cite
|
Sign up to set email alerts
|

Infections of Cerebrospinal Fluid Shunts: Epidemiology, Clinical Manifestations, and Therapy

Abstract: During a 10-year period shunt infections occurred in 27% of the 289 hydrocephalic patients who had cerebrospinal fluid shunts inserted at Children's Hospital Medical Center. The rate of infection did not vary with the type of shunt. Staphylococcus epidermidis and Staphylococcus aureus were responsible for one-half and one-quarter of the infections, respectively. Removal of the infected shunt in conjunction with administration of systemic antibiotics was effective therapy. Use of systemic antibiotics alone was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
216
1
10

Year Published

1975
1975
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 547 publications
(239 citation statements)
references
References 38 publications
10
216
1
10
Order By: Relevance
“…S. epidermidis is the most common cause of prosthetic hip infections (10), cerebrospinal fluid shunt infections (1,12), and prosthetic valve endocarditis (14,15).…”
mentioning
confidence: 99%
“…S. epidermidis is the most common cause of prosthetic hip infections (10), cerebrospinal fluid shunt infections (1,12), and prosthetic valve endocarditis (14,15).…”
mentioning
confidence: 99%
“…Total shunt revision in our series represented 58.1% of shunt procedures which is much higher than the result of Naftel et Shunt-related infections represent 2 to 27% of total shunt procedures (8,15,18,21,22,28,27,30). Shunt revision due to shunt related infection in our study represented 11.22% of the total cases which is slightly higher than the result of Kulkarni et al (26) who reported 10% infection rate after VPS insertion but less than the results of Kinasha et al (13) who reported 24.6% shunt related infection but overall in our elective neurosurgical procedures the incidence of shunt related infection is still accepted.…”
Section: Discussionmentioning
confidence: 51%
“…3,15,35 The clinical consequences of a shunt infection include seizures, psychomotor retardation, reduced intelligence quotient, and increased mortality. 13,22,25,32,37,39 The rate of shunt infection reported varies considerably in the literature, but in recent studies the incidence typically ranges from 5% to 15%, with rates typically higher in high-risk groups such as preterm neonates and patients recently treated for shunt infection. 28,33,34,36,42 Evidence of a shunt infection often manifests within 2 months after surgery.…”
mentioning
confidence: 99%